Don't call me a leader, but I am one: The Dutch mayor and the tradition of bridging-and-bonding leadership in consensus democracies. (April 2017) - Karsten, Niels; Hendriks, Frank
In some democratic contexts, there is a strong aversion to the directive, individualistic and masculine expressions of leadership that have come to dominate the study of political leadership. Such leadership is antithetical to consensus democracies in parts of continental Europe, where the antipathy to leadership has linguistic, institutional as well as cultural dimensions. Political-administrative and socio-cultural contexts in these countries provide little room for heroic expressions of leadership. Consequently, alternative forms of leadership and associated vocabularies have developed that carry profound practical relevance but that have remained underexplored. Based on an in-depth mixed-methods study, this article presents the Dutch mayoralty as an insightful and exemplary case of what can be called 'bridging-and-bonding leadership'; it provides a clear illustration of how understandings of democratic leadership can deviate from the dominant paradigm and of how leading in a consensus context brings about unique practical challenges for office holders. The analysis shows that the important leadership task of democratic guardianship that is performed by Dutch mayors is in danger of being overlooked by scholars of political leadership, as are consensus-oriented leadership roles in other parts of the world. For that reason, a recalibration of the leadership concept is needed, developing an increased theoretical sensitivity towards the non-decisive and process-oriented aspects of the leadership phenomenon. This article specifies how the future study of leadership, as a part of the change that is advocated, can benefit from adopting additional languages of leadership.